2002
DOI: 10.7589/0090-3558-38.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Cytauxzoonosis in a Free-ranging Bobcat (Lynx rufus)

Abstract: In September 2000, a free-ranging bobcat (Lynx rufus) cub was presented to the Kansas State University Veterinary Teaching Hospital (Manhattan, Kansas, USA) in a moribund state with signs of severe anemia and respiratory difficulty. The cub was euthanized. Gross necropsy findings included multifocal atelectasis, splenomegaly, and pericardial effusion. Microscopic examination revealed subacute pulmonary thrombosis, mild vasculitis in the brain, and large schizont-filled macrophages within blood vessels of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 4 publications
2
33
0
1
Order By: Relevance
“…On the basis of 18S rRNA gene sequences analysed in the present study, the C. felis strains responsible for deaths among cats and presumably in bobcats, the natural reservoir host (Nietfeld and Pollock, 2002) in the United States are not genetically distinct from the other American C. felis strains that have been obtained and sequenced from non-fatal cases. However, in some instances rRNA sequence analyses cannot differentiate closely related species, subspecies or strains (Fox et al 1992).…”
Section: Molecular Characterization Of Cytauxzoon Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of 18S rRNA gene sequences analysed in the present study, the C. felis strains responsible for deaths among cats and presumably in bobcats, the natural reservoir host (Nietfeld and Pollock, 2002) in the United States are not genetically distinct from the other American C. felis strains that have been obtained and sequenced from non-fatal cases. However, in some instances rRNA sequence analyses cannot differentiate closely related species, subspecies or strains (Fox et al 1992).…”
Section: Molecular Characterization Of Cytauxzoon Sppmentioning
confidence: 99%
“…However, although bobcats can develop the tissue phase of the pathogen and may die of experimental cytauxzoonosis (Kier et al 1982 ;Blouin et al 1987), it was considered that C. felis could not cause the death of wild bobcats. This view changed when Nietfeld and Pollock (2002) reported a free-living bobcat cub that died of acute cytauxzoonosis. These authors suggested that some bobcats may die each year due to cytauxzoonosis, but these cases remain undetected by current surveillance protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[12][13][14]18 This report describes the neuropathologic changes in 8 cases of feline cytauxzoonosis in domestic cats. Cases of C. felis infection were identified retrospectively in domestic cats that presented for necropsy at the Athens Veterinary Diagnostic Laboratory at The University of Georgia College of Veterinary Medicine between January 2000 and July 2014.…”
mentioning
confidence: 99%
“…The identification of these piroplasms as C. felis was based on their morphology and the prior finding that inoculation of a domestic cat with mononuclear cells from a Florida panther resulted in fatal cytauxzoonosis (Butt et al, 1991). No clinical cytauxzoonosis has been reported from cougars in Florida, but a fatal cytauxzoonosis has been reported in the natural reservoir, the bobcat (Lynx rufus) (Nietfeld and Pollock, 2002), and in a captive white tiger (Panthera tigris) from northern Florida, USA (Garner et al, 1996). Two cases of fatal babesiosis have been reported in cougars translocated from a zoological park in California, USA to Cairo, Egypt (Carpano, 1934).…”
mentioning
confidence: 99%